Profile of F2-Isoprostane Level After 5-Day Administration of Robusta Coffee at a Steady State Dose in Subjects Performing Physical Exercise - Rizky Darmawan; Izzul Mujahidin; Muhammad Fath Alhaqqi Sanis Salamy; Ulul Azmy; Gwenny Ichsan Prabowo; Prayogi Dwina Angga; Mohd Nahar Azmi Mohamed; Lilik Herawati (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to analyze the effect of robusta Dampit coffee on F2-isoprostane levels influenced by ROS due to excessive exercise. This study was an experimental study with a pre- and post-test control group design with coffee administration. The total sample was 18 untrained or sedentary male, divided into two groups: coffee group (COF, n=9) and control/placebo group (PLB, n=9). The COF group was given 2 cups of filtered coffee a day (100 ml/cup) at 12-hour intervals for 5 days. Both groups performed physical exercise with a step test on day 6. Blood samples were collected pre and two hours post exercise. F2-isoprostane concentration was analyzed using the F2-isoprostane biomarker and ELISA to measure the level of lipid peroxidation. Results showed a decrease in F2-isoprostane levels in both COF (pre: 1531.57±278.13 pg/mL; post: 1367.6±230.24 pg/mL; p=0.110) and PLB (pre: 1716.65±501.19 pg/mL; post: 1600.02±500.59 pg/mL; p=0.139) groups with a greater decrease in the COF group. However, this reduction was not significantly different between groups (p=0.734). Although not significantly different, exercising participants tended to have lower F2-isoprostane levels after consuming robusta coffee for five days at a steady state dose. Therefore, further investigation is needed to ascertain the physiological consequences of coffee administration over a longer period of time and its effect on recovery speed.